Sequential Catalytic Conversion of Methyl Oleate Into Short Chain Alkane and Alkene Compounds - Handoko, Donatus Setyawan Purwo; Triyono (PT FORMOSA CENDEKIA GLOBAL, 2024)
Research on the conversion of methyl oleate (Methyl 9-octadecenoate) into shorter chain alkane compounds through the stages of methyl 9-octadecenoate into 1-octadecanol, 1-octadecanol into 1-octadecene and 1-octadecene into alkane compounds and short chain alkenes with a length of C12 > have been done. The conversion process uses ZSiA and Ni/ZSiA catalysts which are placed in a fixed bed system reactor column and operated at temperatures of 400, 450 and 500 oC. ZSiA catalyst was made by washing natural zeolite with distilled water, soaking with 2 M HCl solution, adding 5% Na2SiO3 w/w, soaking with 2 M NH4Cl solution, calcining at a temperature of 500 oC while flowing nitrogen gas for two hours at a flow rate of 20 milliliters per minute; oxidation during a two-hour oxygen flow rate of 20 milliliters per minute; and impregnation of Ni metal onto the catalyst sample's surface using Ni(NO3)2 6H2O metal 2% w/w. Subsequently, reduction was done for two hours while hydrogen gas was flowing at a rate of 20 mL per minute. The resultant catalyst was subjected to various analyses, including AAS analysis for metal cation content, gravimetric analysis for acidity, NOVA 1000 surface area analyzer for specific surface area, and X-ray diffractometer (XRD, Shimadzu-6000) analysis for crystallinity